An Aqueous Conducting Redox‐Polymer‐Based Proton Battery that Can Withstand Rapid Constant‐Voltage Charging and Sub‐Zero Temperatures. Issue 24 (31st March 2020) - Strietzel, Christian; Sterby, Mia; Huang, Hao; Strømme, Maria; Emanuelsson, Rikard; Sjödin, Martin
Abstract: Electrodes based on organic matter operating in aqueous electrolytes enable new approaches and technologies for assembling and utilizing batteries that are difficult to achieve with traditional electrode materials. Here, we report how thiophene‐based trimeric structures with naphthoquinone or hydroquinone redox‐active pendent groups can be processed in solution, deposited, dried and subsequently polymerized in solid state to form conductive (redox) polymer layers without any additives. Such post‐deposition polymerization offers efficient use of material, high mass loading (up to 10 mg cm −2 ) and good flexibility in the choice of substrate and coating method. By employing these materials as anode and cathode in an acidic aqueous electrolyte a rocking‐chair proton battery is built. The battery shows good cycling stability (85 % after 500 cycles), withstands rapid charging, with full capacity (60 mAh g −1 ) reached within 100 seconds, allows for direct integration with photovoltaics, and retains its favorable characteristics even at −24 °C. Abstract : Combining naphthoquinone or hydroquinone redox‐active pendent groups, an all‐organic battery was designed to operate in aqueous electrolyte. This battery does not only show good capacity retention over 500 cycles but can also be charged ultra‐rapidly using a potential step, enabling easy integration with an organic solar cell.